Supracapsular glued intraocular lens in progressive subluxated cataracts: Technique to retain an intact vitreous face. Issue 3 (March 2017) - Jacob, Soosan; Narasimhan, Smita; Agarwal, Amar; Mazzotta, Cosimo; Rechichi, Miguel; Agarwal, Athiya
Abstract : N/A: We describe a technique to prevent late intraocular lens (IOL) subluxation and dislocation that can be associated with progressive zonulopathy. Supracapsular glued IOL fixation is done to retain an intact anterior hyaloid face and avoid vitreous disturbance while providing stable long‐term IOL fixation. Phacoemulsification is followed by glued IOL implantation above intact anterior and posterior capsules. Sclerotomies are created ab interno in a supracapsular plane under diametrically opposite lamellar scleral flaps without entering the vitreous cavity. Haptics are externalized in the supracapsular plane and tucked into intrascleral tunnels. Intraoperative or postoperative posterior capsulorhexis or capsulotomy and anterior capsule relaxing cuts can prevent capsule phimosis.